Impact of a Prospective Audit and Feedback Antimicrobial Stewardship Program at a Veterans Affairs Medical Center: A Six-Point Assessment. - Haley J Morrill; Aisling R Caffrey; Melissa M Gaitanis; Kerry L LaPlante (PLoS ONE)
Background Prospective audit and feedback is a core antimicrobial stewardship program (ASP) strategy; however its impact is difficult to measure. Methods Our quasi-experimental study measured the effect of an ASP on clinical outcomes, antimicrobial use, resistance, costs, patient safety (adverse drug events [ADE] and Clostridium difficile infection [CDI]), and process metrics pre- (9/10-10/11) and post-ASP (9/12-10/13) using propensity adjusted and matched Cox proportional-hazards regression models and interrupted time series (ITS) methods. Results Among our 2,696 patients, median length of stay was 1 day shorter post-ASP (5, interquartile range [IQR] 3-8 vs. 4, IQR 2-7 days, p<0.001). Mortality was similar in both periods. Mean broad-spectrum (-11.3%), fluoroquinolone (-27.0%), and anti-pseudomonal (-15.6%) use decreased significantly (p<0.05). ITS analyses demonstrated a significant increase in monthly carbapenem use post-ASP (trend: +1.5 days of therapy/1,000 patient days [1000PD] per month; 95% CI 0.1-3.0). Total antimicrobial costs decreased 14%. Resistance rates did not change in the one-year post-ASP period. Mean CDI rates/10,000PD were low pre- and post-ASP (14.2 ± 10.4 vs. 13.8 ± 10.0, p = 0.94). Fewer patients experienced ADEs post-ASP (6.0% vs. 4.4%, p = 0.06). Conclusions Prospective audit and feedback has the potential to improve antimicrobial use and outcomes, and contain bacterial resistance. Our program demonstrated a trend towards decreased length of stay, broad-spectrum antimicrobial use, antimicrobial costs, and adverse events.